Capsaicin-Induced Skin Desensitization Differentially Affects A-Delta and C-Fiber-Mediated Heat Sensitivity - van Neerven, Sabien G. A.; Mouraux, André (Frontiers in Pharmacology, 2020)
Localized neuropathic pain can be relieved following the topical application of high-concentration capsaicin. This clinical effect is thought to be related to the temporary desensitization of capsaicin- and heat-sensitive epidermal nociceptors. In healthy volunteers, the localized and selective desensitization of capsaicin-sensitive afferents induced by topical capsaicin can be used to study perceptual reorganization following deafferentation. The objective of the present study was to explore how different types of thermosensitive afferents in the skin surrounding the capsaicin-denervated area respond to the selective ablation of capsaicin-sensitive fibers. The volar forearm of 20 healthy volunteers were treated with a high-concentration capsaicin patch for 1 hour. Transient heat, warm and cold stimuli designed to activate Aδ- and C-fiber thermonociceptors, C-fiber warm receptors and Aδ-fiber cold receptors were applied to the skin before and after treatment at days 1, 3 and 7. Reaction times, intensity ratings and quality descriptors were collected. The stimuli were applied at and around the capsaicin-treated area to map the changes in thermal sensitivity. We found that topical capsaicin selectively impairs heat sensitivity without any concomitant changes in cold sensitivity. Most interestingly, we observed a differential effect on the sensitivity to thermal inputs conveyed by Aδ- and C-fibers. Reduced sensitivity to Aδ-fiber-mediated heat was restricted to the capsaicin-treated skin, whereas reduced sensitivity to C-fiber-mediated heat extended well beyond the treated skin. Moreover, the time course of the reduced sensitivity to C-fiber-mediated input was more prolonged than the reduced sensitivity to Aδ-fiber-mediated input.